2023
DOI: 10.3390/pharmaceutics15112583
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Films as Transmucosal Drug Delivery Systems

Ana Clara Wada de Carvalho,
Natália Floriano Paiva,
Isabella Kriunas Demonari
et al.

Abstract: Pharmaceutical films are polymeric formulations used as a delivery platform for administration of small and macromolecular drugs for local or systemic action. They can be produced by using synthetic, semi-synthetic, or natural polymers through solvent casting, electrospinning, hot-melt extrusion, and 3D printing methods, and depending on the components and the manufacturing methods used, the films allow the modulation of drug release. Moreover, they have advantages that have drawn interest in the development a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 141 publications
(253 reference statements)
0
1
0
Order By: Relevance
“…An application in dentistry of fast-dissolving films is the obtaining of sux formulations containing chlorhexidine by the solvent casting method. After in vitro decay analyses, antimicrobial activity tracking and stability studies, as well as using infrared spectroscopy with Fourier modifications, it was concluded that chlorhexidine films offer promising results in the management of oral diseases [64][65][66][67].…”
Section: Fast-dissolving Oral Films (Fdof)mentioning
confidence: 99%
“…An application in dentistry of fast-dissolving films is the obtaining of sux formulations containing chlorhexidine by the solvent casting method. After in vitro decay analyses, antimicrobial activity tracking and stability studies, as well as using infrared spectroscopy with Fourier modifications, it was concluded that chlorhexidine films offer promising results in the management of oral diseases [64][65][66][67].…”
Section: Fast-dissolving Oral Films (Fdof)mentioning
confidence: 99%